PENGARUH STORE EVIRONMENT TERHADAP CUSTOMER EXPERIENCE DAN REPURCHASE INTENTION PADA MITOS KOPI COFFEE SHOP RENON - Bertha, Devina; Rahanata, Gede Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023, 2023)
The coffee shop business is one of the most popular businesses during the Covid-19 pandemic. Not many businesses can survive during the pandemic, but Myth Coffee is able to retain its customers despite declining sales. This study aims to analyze the effect of Store Environment on Customer Experience and Repurchase Intention on the Myth of Coffee Shop Renon Coffee. The number of samples in this study were 130 respondents. Data obtained from the distribution of research questionnaires. The data that has been collected is then analyzed using path analysis techniques. The results of the study found that the store environment had a significant positive effect on repurchase intention on the Myth of Kopi Coffee Shop Renon. Store environment has a significant positive effect on customer experience at the Myth of Kopi Coffee Shop Renon. Customer experience has a significant positive effect on repurchase intention on the Myth of Kopi Coffee Shop Renon. Customer experience plays a significant positive role in mediating the store environment on repurchase intention in the Myth of Kopi Coffee Shop Renon. Myth of Kopi Coffee Shop Renon can do the right interior decoration will provide a new experience for consumers so that they can leave a positive impression on consumers' minds and in the long run are interested in making repurchases.